Gestión de recuperación de cartera del periodo 2018 del Banco Comunitario – Junquillo - Ulloa Fernández, Yelitza Germania (2020)
The Junquillo Community Bank is an institution, made up of a group of people from the locality, the capital comes from the contributions and savings of the members with the purpose of earning economic benefits (profits) for its members, it grants credits, for a determined term , to the inhabitants of the enclosure and neighboring places under the statute of the bank approved by the assembly. This case study is based on the incidence that the Management of Recovery of Overdue Portfolio has on agricultural and consumer loans that have not been paid in full within the specified terms, or that, having been restructured or renewed, continue to default, generating a past due portfolio. This work is framed in the research line Financial Management and Social Commitment which is assimilated to the problem that is located in the coffee plantation cooperative, verifying what is stipulated in the lines of investigation of the accounting school, audit and finance.